To find the equation of the line in slope-intercept form \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept, we can use the point-slope form of the line equation, which is given by:
\[ y - y_1 = m(x - x_1) \]
where \( (x_1, y_1) \) is a point on the line, and \( m \) is the slope.
Given that the point is \( (-5, 3) \) and the slope \( m \) is \( -1 \), we can substitute these values into the point-slope form:
\[ y - 3 = -1(x + 5) \]
Now, we can simplify this equation step-by-step:
- Distribute the slope on the right side:
\[ y - 3 = -x - 5 \]
- Add 3 to both sides to isolate \( y \):
\[ y = -x - 2 \]
Now we have the equation of the line in slope-intercept form. Therefore, the correct response is:
\[ y = -x - 2 \]
So, the answer is: y = −x − 2.